Bedenin anlamlarına Türk mitleri ve destanları odaklı kültürel bir yaklaşım - Sezer, Ayşe (My University, 2023)
Beden, birçok disiplin tarafından ele alınarak incelenmiş ve incelenmeye devam eden bir kavramdır. Bedenin hem pozitif hem de sosyal bilimciler tarafından ele alınması, insanın bedeni sayesinde var olması ve ona kültürel anlamlar yüklemesiyle alakalıdır. Beden yüzyıllar boyunca hem maddi hem de manevi bir varlık olagelmiştir. Özellikle insanın en değerli ve ebedi giysisi beden sayılmış; insan yahut hayvan öldüğünde, yaşıyormuş izlenimi vermek ya da bir koruyuculuk görevi atfetmek adına bedenler ya mumyalanmış ya da postları saklanmıştır. Aynı zamanda beden sağlığın yerinde olduğunun/ olmadığının bir göstergesi ve canlılığın bir tezahürü sayılarak insanın dünyadaki varlığının en somut hali olarak kabul edilmiştir. Beden, dış dünya ile olan iletişimin ilk ve en önemli unsurudur. Konuşmadan anlaşmanın ve kendini/ toplumunu anlatmanın en önemli yolu yani bir sözsüz iletişim modelidir. Bu sebeple beden üzerindeki her bir işaretin/ dövmenin, her davranışın ve giyinişin bir anlamı bulunmakta, insanlar iç ve sosyal dünyalarını her türlü bedensel hareket üzerinden dışarıya göstermektedir. Aynı zamanda insan yahut hayvan bedenindeki her uzuv ve organın, biyolojik yahut kültürel bir işlevi/ anlamı hep olmuştur. Bu işlevsellik/ işlevsizlik durumunda beden ve bedenin parçaları anlam/ anlamsızlık kazanmıştır. Bedenin yara alması ya da bir organın işlevini yitirmesi, insan ve hayvanları işlevsiz ya da eksik pozisyonuna düşürmektedir. Örneğin yüze alınan bir darbe ya da yüzde oluşan bir yara, doğrudan kimliğe zarar vermekte; kişiyi kimliksizleştirmektedir. Bu sebeple bedenin kültürel boyutunun araştırılması, insan zihnini ve kültürel yapıları anlamak adına önem arz etmektedir. Çünkü her topluluğun bedene bakış açısında ortaklıklar bulunmakla birlikte, bedenle ilgili farklı düşünceler ya da bedene yüklenen farklı anlamlar da olmuştur. Bedene dair çalışmalar ilk olarak tıbbi, felsefi ve etnografik bağlamda olsa da bedenin tarihi ve bedene yüklenen anlam, en az insanlık tarihi kadar eskidir. Toplumların din ve mitolojilerinde farklı şekillerde karşımıza çıkan beden; her zaman inancın ve kültürün bir tezahürü olmuştur. Folklorik bağlamda ise beden konusuna, ilk kez 1989 yılında Katharine Young değinmiş, bedene dönük folklorik çalışmaları adlandırmak için de “bodylore” (beden folkloru) terimini önermiştir. Beden etrafında, yaratılışından yok oluş sürecine kadar çeşitli anlatılar/ inanışlar geliştirilmiş; özellikle insan bedeni, dünya ile özdeşleşerek üç boyutlu dünya modelini X olarak simgelenmiştir. Bedenin alt kısmı, cehennemi/ alt dünyayı; vücudu, orta dünyayı; baş kısmı ise üst dünyayı yani cenneti temsil etmektedir. Bu sebeple bedene yüklenen anlamlar sadece somut değil, soyut da olmuştur. Bu sebeple beden kavramına tek bir disiplini esas alarak yaklaşmak, özellikle günümüz bilgi birikimiyle yeterli olmayacaktır. Tek bir kültür üzerinden bedene dair algılara ulaşmak yetersiz kalacağı için çalışmamızda yer yer farklı kültürlerin anlatılarına da yer verilecek ve karşılaştırmalı bir kültürel çalışma yapılacaktır. Çalışmamızda Türk sözlü kültürü içerisindeki mit ve destan türü üzerinden kısmen karşılaştırmalı beden tasvirlerinin kültürel bağlamda yorumları yapılacak, anlamları ve işlevleri üzerinde durulacaktır. Ayrıca literatür tarama yöntemi kullanılmakla birlikte kuramsal anlamda yorumsamacı yaklaşım/ hermenötik denemesi yapılacaktır. Çalışmada anlatılardaki bedenin yerinin diğer milletlerin halk anlatıları karşısındaki yerinin daha iyi bir şekilde belirlenebilmesi adına karşılaştırma yöntemine de başvurulacaktır. Ayrıca anlatılardaki beden, tip ve karakterlerin beden tasvirlerinin bir yorumunu yapmak, hem metinlerin modern anlamda yeniden bir yorumu hem de günümüz bilgi birikimi ile geçmişe tekrar bakmak adına bir önem teşkil etmektedir. Kullanılacak yorumsamacı yaklaşımın temelinde olay, olgu ve kavramlara çok yönlü bir şekilde bakma fikri vardır. Bu sebeple kültürel bağlamda bir okuma çalışması ile zengin bir literatür taramasına gidilerek; anlatılardaki beden okumaları sadece tespit boyutunda kalmayacak; bedene yüklenen anlamların temellerine inilecektir.

The body is a concept that has been studied extensively and still continues to be observed under many disciplines to this day. The fact that the body has been a subject of consideration both by scientists of positive and social backgrounds is a situation related to the survival of the human race thanks to the collective notion of the body and to the process of assigning various cultural meanings unto it. The body has served as both a material and a spiritual term for centuries. In particular, the most valuable and eternal of all the garments of a man was considered to be the body. In the event that a person or an animal dies, the bodies are either mummified or their skins are hidden away to give the impression of them being alive and maybe to fulfill the role of a guardian. In short, the body has been accepted as the most concrete form of human existence in the world and as an indicator of good health or some manifestation of vitality. The body is the first and foremost element of communication with the outside world. It is a nonverbal communication model, that is, the most important way of understanding and means of expression in regards to individuals and/ or the society in general. For this reason every visible sign/ tattoo, every displayed behavior and styles of dresses related to the body involve some degree of meaning. In accordance, people project their inner and social worlds to the outside environment through various kinds of bodily movements. At the same time, every limb and organ in the human or animal body always had a biological or cultural function/ meaning. In these states of functionality or dysfunction, the body and its parts have gained meanings or they have plunged into meaninglessness. Injury to the body or the loss of a function occurring in various organs puts humans and animals in dysfunctional or deficient positions of being. For example, an act of aggression to the face or a visible wound on it directly harms one’s identity and results in the depersonalization of the individual. For this reason, researching the cultural dimensions of the body presents an academic importance due to the necessity of understanding the human mind and the cultural structures of humanity. Furthermore, there have been emergent commonalities in the perspectives of each community with regards to the body and yet there have also been different thoughts on the concept of the body or on the numerous meanings attributed to it. Although studies on the body first presented themselves in medical, philosophical and ethnographic contexts, the history of XII the body and the related meanings attributed still are as old as the very history of humanity. The body, which appears in different forms within the religious and mythological aspects of societies, has always remained as a manifestation of faith and of culture. Within the folkloric context, it can be said that Katharine Young was the first to study the body during 1989. He also suggested the word bodylore (body folklore) to coin the term which was to cover the folkloric studies conducted on the body. Various narratives and aspects of numerous beliefs have been developed around the body, from its creation to the destruction stage of it. In particular, the human body is identified with the world and symbolized a three-dimensional model of said world. Accordingly the lower body was associated with hell/ lower world, main parts of the body with the middle earth and with the head part representing the upper world, that is, heaven. For this reason, the meanings attributed to the body have not only been devoid of concrete descriptions but also of an abstract quality. So it is apparent that approaching the concept of body on the basis of a single discipline will not be a sufficient method, especially with the advancements resulting from knowledge gained thanks to recent research. Since it will be insufficient to reach a holistic perception of the body through a single culture, the narratives of different cultures will be included in our study and a comparative cultural study will also be carried out. In our study, the comparative basis of bodily descriptions will be interpreted within their own cultural context, and their meanings accompanied by their functions will be emphasized through the mythical and epic types contained within the Turkish oral culture. In addition to the literature review method which will be used, a theoretical hermeneutic approach / hermeneutic experiment will also be utilized. In the study, the comparison method also will be applied in order to better determine the place of the body with the elements being the Turkish naratives and other folk narratives of foreign contexts. In addition, interpreting descriptions of the body, its types and related characters in such narratives is important both for a modern interpretation of the texts and for looking back at the past utilizing the perspective of recency. The basis of the hermeneutic approach to be used is the idea of observing events, facts and concepts in a multifaceted manner. As such, going through a rich literature review with a reading study being conducted within the XIII related cultural contexts, bodily readings in narratives will not remain not only in the dimensions of detection and/ or perception, they shall also constitute the foundations of the meanings as they have been attributed to the body.
Keywords: Beden; Beden, İnsan; Beden, İnsan, Edebiyatta; Body; Body, Human; Body, Human, in literature; Culture; destan; epic; folklor; folklore; Kültür; legend; mit; myth; oral culture; sözlü kültür; written culture; yazılı kültür